Comparison of yield of Norway spruce (Picea abies) and Sitka spruce (Picea sitchensis) in Skorradalur, West Iceland - Reynisson, Valdimar (2011)
Iceland has suffered from massive deforestation since the Vikings settled on the island in 874. The woodland cover has gone from 25-30% to 1 %. Since the beginning of the 20th century, effort has been made to regain the forest. In these afforestation efforts many tree species have been used both indigenous and exotic. Coniferous species have played a major role in this afforestation. Species such as Siberian larch, Norway spruce, Sitka spruce and various pine species have been important in these efforts. The two spruce species mentioned earlier have both been very important in the afforestation of Iceland. However, the usage of Norway spruce has declined through time whereas usage of Sitka spruce has increased. This study was carried out in a forested area in West Iceland owned by the Icelandic forest service. The aim of the study was to find out how much yield difference is between Norway spruce and Sitka spruce in this area. The result shows a very big difference between those species and in all aspects the Sitka spruce has higher values. The average difference for stands 46-55 years old for total mean annual increment this is 3,7m3/ha/year or 86,9% more for Sitka spruce compared to Norway spruce.